Long-term outcomes of COVID-19 convalescents: An 18.5-month longitudinal study in Wuhan. (February 2023) - Guo, Yi; Wang, Hao; Xiao, Mingzhong; Guan, Xin; Lei, Yanshou; Diao, Tingyue; Long, Pinpin; Zeng, Rui; Lai, Xuefeng; Cai, Hao; You, Yutong; Wen, Yuying; et al.
Highlights: Most participants had an improved physical and psychological health status. We observed sequelae symptoms in 45.2% of participants at 18.5 months. We observed abnormal chest computed tomography patterns in about 30% of participants at 18.5 months. The convalescents still had mild depression or anxiety disorders at the last visit. Abstract: Objectives: This study aimed to describe the full scope of long-term outcomes and the ongoing pathophysiological alterations among COVID-19 survivors. Methods: We established a longitudinal cohort of 208 COVID-19 convalescents and followed them at 3.3 (interquartile range [IQR]: 1.3, 4.4, visit 1), 9.2 (IQR: 9.0, 9.6, visit 2), and 18.5 (IQR: 18.2, 19.1, visit 3) months after infection, respectively. Serial changes in multiple physical and psychological outcomes were comprehensively characterized. We, in addition, explored the potential risk factors of SARS-CoV-2 antibody response and sequelae symptoms. Results: We observed continuous improvement of sequelae symptoms, lung function, chest computed tomography (CT), 6-minute walk test, and the Borg dyspnea scale, whereas sequelae symptoms (at least one) and abnormal chest CT patterns still existed in 45.2% and about 30% of participants at 18.5 months, respectively. Anxiety and depression disorders were alleviated for the convalescents, although depression status was sustained for a longer duration. Conclusions: Most COVID-19 convalescents had an overall improved physical and psychological health status, whereas sequelae symptoms, residual lesions on lung function, exercise impairment, and mental health disorders were still observed in a small proportion of participants at 18.5 months after infection. Implementing appropriate preventive and management strategies for the ever-growing COVID-19 population is warranted.